PENGARUH PENGETAHUAN PERPAJAKAN, KESADARAN PAJAK, DAN PEMBERIAN HADIAH TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN DI KOTA SURAKARTA - Michelle Rayna; Hernawati Pramesti (Widya Balina, 2025)
This study aims to examine the influence of tax knowledge, taxpayer awareness, and reward incentives on individual taxpayer compliance in paying Land and Building Tax (PBB) in the city of Surakarta. The data used in this research are primary data obtained through questionnaires distributed to PBB taxpayers in Surakarta using a purposive sampling technique. A total of 150 questionnaires were distributed using a Likert scale, and after a validation and screening process, 100 questionnaires were deemed valid and eligible for data analysis. The data were analyzed using the multiple linear regression method. The results indicate that tax knowledge and taxpayer awareness have a significant effect on individual taxpayer compliance in paying PBB, while reward incentives do not have a significant effect on compliance. These findings highlight the importance of enhancing taxpayers' understanding and awareness to improve compliance with local tax obligations.